Food Safety Within the Household - Lucianna Grasso; George L. Baker; Renée M. Goodrich-Schneider; Keith R. Schneider (EDIS, 2012)
Although food safety education is well established, people still become infected with foodborne illnesses by practicing unsafe behaviors in their kitchen. People who know the basics of home food safety may not always put theory into practice. Consumers must learn more about how food becomes unsafe to eat and modify their current beliefs and behaviors. This 5-page fact sheet was written by Lucianna Grasso, George L. Baker, Renée M. Goodrich-Schneider, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, October 2012.